Evaluation of the accuracy of serum MMP-9 as a test for colorectal cancer in a primary care population - Wilson, S; Wakelam, M; Hobbs, R; Ryan, A; Dunn, J; Redman, V; Patrick, F; Colbourne, L; Martin, A; Ismail, T (BioMed Central, 2006)
Background: Bowel cancer is common and is a major cause of death. Meta-analysis of randomised controlled trials estimates that screening for colorectal cancer using faecal occult blood (FOB) test reduces mortality from colorectal cancer by 16%. However, FOB testing has a low positive predictive value, with associated unnecessary cost, risk and anxiety from subsequent investigation, and is unacceptable to a proportion of the target population. Increased levels of an enzyme called matrix metalloproteinase 9 (MMP-9) have been found to be associated with colorectal cancer, and this can be measured from a blood sample. Serum MMP-9 is potentially an accurate, low risk and cost-effective population screening tool. This study aims to evaluate the accuracy of serum MMP-9 as a test for colorectal cancer in a primary care population. Methods/Design: People aged 50 to 69 years, who registered in participating general practices in the West Midlands Region, will be asked to complete a questionnaire that asks about symptoms. Respondents who describe any colorectal symptoms (except only abdominal bloating and/or anal symptoms) and are prepared to provide a blood sample for MMP9 estimation and undergo a colonoscopy (current gold standard investigation) will be recruited at GP based clinics by a research nurse. Those unfit for colonoscopy will be excluded. Colonoscopies will be undertaken in dedicated research clinics. The accuracy of MMP-9 will be assessed by comparing the MMP-9 level with the colonoscopy findings, and the combination of factors (e.g. symptoms and MMP-9 level) that best predict a diagnosis of malignancy (invasive disease or polyps) will be determined. Discussion: Colorectal cancer is a major cause of morbidity and mortality. Most colorectal cancers arise from adenomas and there is a period for early detection by screening, but available tests have risks, are unacceptable to many, have high false positive rates or are expensive. This study will establish the potential of serum MMP-9 as a screening test for colorectal cancer. If it is confirmed as accurate and acceptable, this serum marker has the potential to assist with reducing the morbidity and mortality from colorectal cancer.